DETERMINAN TAX AVOIDANCE DENGAN KEPEMILIKAN INSTITUSIONAL SEBAGAI PEMODERASI (STUDI PADA PERUSAHAAN PERTAMBANGAN) - Prasetiyo, Toni; Djaddang, S.; Ahmar, N. (Program Studi Akuntansi FPEB UPI, 2021)
The purpose of this research is to examine the effect of independent comissioner, audit committee, and audit quality on tax avoidance which moderated by institutional ownership at mining companies in Indonesia Stock Exchange. The samples in this study amounted to 33 mining company in Indonesia Stock Exchange period 2017-2019. The test results show that independent comissioner and audit quality have a negative effect on tax avoidance. Meanwhile audit committee has a positive effect on tax avoidance. Furthermore, Institutional ownership moderate independent comissioner, audit committee, and audit quality on tax avoidance (quasi moderation).